Prisoners of war in contemporary conflict - Schmitt, Michael N.; Koschnitzky, Christopher J. (New York, NY : Oxford University Press, 2023)
Examines the rules governing the designation and treatment of POWs in contemporary conflict. Each chapter examines specific topics around POWs that the contributors identify as unsettled, operationally problematic, or inadequately addressed in existing literature.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 28, 2023).
Keywords: Convention Relative to the Treatment of Prisoners of War -- (1949 August 12); Prisoners of war -- Legal status, laws, etc; Law; International law